A210 DECLINE IN HEPATITIS B QUANTITATIVE SURFACE ANTIGEN LEVELS IN CHRONIC HEPATITIS B PATIENTS ON TREATMENT WITH NUCLEOS(T)IDE ANALOGUES. (4th March 2021) - Stach, J; Zhao, I; Frolkis, A; Haylock-Jacobs, S; Israelson, H; Pinto, J; Williams, S; Swain, M; Stinton, L; Aspinall, A; Borman, M; Sadler, M D; et al.
Abstract: Background: The Hepatitis B virus (HBV) affects over 250 million people worldwide and can lead to cirrhosis and hepatocellular carcinoma. HBV surface antigen (HBsAg) quantification is increasingly used to predict disease activity and treatment response. As there is no virologic cure, clinicians are seeking a "functional cure", or HBsAg loss, as a guide to safely stopping nucleos(t)ide analogue therapy. Tenofovir Disoproxil Fumarate (TDF) and Entecavir (ETV) are first line therapy but require prolonged treatment to achieve HBsAg clearance. Aims: To assess the association between nucleos(t)ide therapy and decline in quantitative HBsAg (qHBsAg) in patients with HBV from Calgary, Alberta. Methods: A retrospective review of adult patients with chronic HBV, followed at the University of Calgary Liver Clinic, was conducted between January 2012 and October 2020. Patients were excluded if treatment was discontinued or changed, only had a single qHBsAg measurement, or were co-infected with hepatitis C virus, hepatitis delta virus, or HIV. Patients were stratified according to therapy with TDF, ETV, or no treatment. To identify associations between mean changes in qHBsAg by medication exposure, one-way ANOVAs and t-tests were performed. Results were reported as means and 95% confidence intervals (CI). The median time from initial qHBsAg to most-recent was calculated. Results: 187 patients were included in the final analysis (Table 1). 77 were excluded for being on more than one medication over the study period, 10 were excluded due to discontinuation of treatment, and 195 were excluded for single qHBsAg measurements. The mean qHBsAg decline was -750.04 IU/mL (95% CI -1311.58, -188.50) in the TDF group (n=45) and -309.20 IU/mL (95% CI -600.90, -17.50) in the ETV group (n=35) (p=0.20). In the no treatment group (n=107), the mean qHBsAg increased by 711.29 IU/mL (95% CI -600.78, 2023.80)(Figure 1). The median time from initial qHBsAg to most-recent was 980 days. Conclusions: Quantitative HBsAg levels declined in patients on TDF and ETV, but increased in untreated patients. Although HBsAg levels showed a trend for greater decline in TDF-treated patients, results failed to reach statistical significance, and may be affected by overall treatment duration. Future studies will explore medication use as a time-varying covariate to identify how change in treatment influences changes in HBsAg over time. Funding Agencies: None